Use of palm oil cake in diets for slow growing chickens - Arruda, Janaína de Cássia Braga; Fonseca, Lívia Anália Bentes da; Barata, Yan Mathews Leray; Leite, Brenda Kelly Viana; Manno, Maria Cristina; Lima, Kedson Raul de Souza (Medicina Veterinária, 2020)
Looking for food alternatives for slow-growing broiler chickens is a necessity to boost production, which is mainly conducted by small and medium producers linked to family farming, especially in the Amazon region. For this reason, the objective was to evaluate the potential use of Palm Oil Cake (POC) as an alternative ingredient in the feeding of slow-growing broiler chickens up to 28 days of age. We used 416 male French Red-Naked Neck chicks, in a completely randomized experimental design with four treatments (0, 10, 15, and 20% of POC inclusion) with eight replicates each. The performance of the birds, allometry of the digestive organs and the economic analysis of the diets were evaluated. It is concluded that POC can be included in the diets of slow growing broiler chickens, up to 28 days, in up to 15% without causing damage in their performance, without negatively modifying the allometry of the digestive organs and without economic disadvantages to the producer.